2012
DOI: 10.1073/pnas.1217659109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of copy number variations (CNVs) on long-range gene regulation at the HoxD locus

Abstract: Copy number variations are genomic structural variants that are frequently associated with human diseases. Among these copy number variations, duplications of DNA segments are often assumed to lead to dosage effects by increasing the copy number of either genes or their regulatory elements. We produced a series of large targeted duplications within a conserved gene desert upstream of the murine HoxD locus. This DNA region, syntenic to human 2q31-32, contains a range of regulatory elements required for Hoxd gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…Interestingly, the regulatory properties of these regulatory ensembles are in part dictated by the relative distribution of the different modules and of their target gene on the genome [41,137], showing again the influence of the structural organization on the regulatory output.…”
Section: From Enhancer Modules To Structural/regulatory Ensemblesmentioning
confidence: 97%
“…Interestingly, the regulatory properties of these regulatory ensembles are in part dictated by the relative distribution of the different modules and of their target gene on the genome [41,137], showing again the influence of the structural organization on the regulatory output.…”
Section: From Enhancer Modules To Structural/regulatory Ensemblesmentioning
confidence: 97%
“…Furthermore, it was shown that SVs could interfere with gene regulation by disrupting genomic architecture necessary for proper enhancer-promoter interactions. Such rearrangements can result in loss of WT interactions and/or ectopic enhancer-promoter interactions, thereby resulting in gene misexpression (Montavon et al, 2012;Spielmann et al, 2012;Spielmann and Mundlos, 2013). To discriminate between these multiple effects and to study their complex molecular pathology in vivo modeling of SVs is required.…”
Section: Introductionmentioning
confidence: 99%
“…4C requires much less sequencing to achieve a high resolution but limits the analysis to a single viewpoint. Because of its high resolution and low production cost, 4C has been extensively used to explore the regulatory microarchitecture of specific loci and as a proxy to recapitulate and assess TADs structure and variability (Montavon et al 2012;Andrey et al 2013;Ghavi-Helm et al 2014;Lupianez et al 2015;Acemel et al 2016).…”
Section: Berlin Germanymentioning
confidence: 99%